2017
DOI: 10.1016/j.biortech.2016.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable biobutanol production from pineapple waste by using Clostridium acetobutylicum B 527: Drying kinetics study

Abstract: Present investigation explores the use of pineapple peel, a food industry waste, for acetone-butanol-ethanol (ABE) production using Clostridium acetobutylicum B 527. Proximate analysis of pineapple peel shows that it contains 35% cellulose, 19% hemicellulose, and 16% lignin on dry basis. Drying experiments on pineapple peel waste were carried out in the temperature range of 60-120°C and experimental drying data was modeled using moisture diffusion control model to study its effect on ABE production. The produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(28 citation statements)
references
References 42 publications
(45 reference statements)
2
23
0
1
Order By: Relevance
“…It has been reported that during the commercial production of pineapple juice around 20-40% of wastes are generated by FPP and FPC (Khedkar et al 2017). This percentage is similar to the one obtained in this research and has led to research for which these wastes are used as substrates in fermentative and hydrolytic processes to obtain bioactive compounds (Kaprasob et al 2017 reported that 96% of the total pineapple wastes correspond to organic material and 4% to inorganic, which potentiates its use in bioprocesses.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…It has been reported that during the commercial production of pineapple juice around 20-40% of wastes are generated by FPP and FPC (Khedkar et al 2017). This percentage is similar to the one obtained in this research and has led to research for which these wastes are used as substrates in fermentative and hydrolytic processes to obtain bioactive compounds (Kaprasob et al 2017 reported that 96% of the total pineapple wastes correspond to organic material and 4% to inorganic, which potentiates its use in bioprocesses.…”
Section: Resultssupporting
confidence: 84%
“…The residues generated during the processing of the fresh peel of the pineapple (FPP), Fresh core of the pineapple (FCP), and crown represent between 45 and 65% of the total weight of the fruit; about 76% of this waste is fibre, 99.2% is the insoluble fraction, and 0.8% is the soluble fraction (Selani et al 2014). These residues have been used in several ways (Difonzo et al 2018) including the use of pineapple wastes as substrates to obtain bioactive compounds such as biopolymers (Vega-Castro et al, 2016), polyphenols (Sepúlveda et al, 2018), biohydrogen, biogas, and alcohols such as ethanol or butanol (Khedkar et al, 2017), which have the potential for industrial application. Among the evaluated residues, the pineapple peel is outstanding due to the high concentration of reducing sugars (97 g L À1 ) obtained through the application of acid hydrolysis as a pre-treatment (Vega-Castro et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Roda et al [7], pineapple peel waste is made of 35-50% cellulose, 20-35% hemicellulose, and 5-30% lignin. Manisha et al [8] have recently reported a content of 35% cellulose, 19%…”
Section: Introductionmentioning
confidence: 98%
“…Estudos tem sido realizados para a aplicação de subprodutos industriais do abacaxi como as cascas, utilizadas na produção de bolos ricos em fibras (MARTIN et al, 2012), em hambúrgueres bovinos enriquecidos com subprodutos de abacaxi como substitutos de gorduras , na fermentação e produção de biobutanol (KHEDKAR et al, 2017) e a farinha das cascas que podem ser empregadas na produção de barras de cerais (DAMASCENO et al, 2016). Com isso, torna-se necessário garantir que o consumo dos subprodutos seja seguro antes de aplicá-los em qualquer produto alimentício.…”
Section: Subprodutos De Abacaxi (Ananas Comosus L Merrill)unclassified